Feminist Interpretation of Qur’an Surah al-Nisa’ verse 34: An Educational Study on Gender Relations, Structural Violence and the Protection of Women’s Rights - Siregar, Muhammad Sururi Alfajri Wannahar; Zein, Achyar; Astuti, Rahayu Fuji (Ahlussunnah: Journal of Islamic Education, 2025)
Issues of gender inequality and violence against women remain significant challenges across various societal strata, even within communities that strongly uphold religious values. This research critically re-examines Surah al-Nisa’ verse 34 through the lens of feminist tafsir (exegesis). Its aim is to deconstruct imbalanced gender relations and analyze their implications for structural violence experienced by women in Muslim societies. This particular verse is often used as a theological justification for male dominance over women in domestic and social spheres, thereby potentially perpetuating gender-based inequality and violence. The study employs feminist gender hermeneutics, utilizing a critical approach to both the text and its context, along with an analysis of the socio-cultural constructions that inform traditional interpretations. This research emphasizes the importance of reading the text with a strong bias towards gender justice and the protection of women’s rights, considering the verse’s historical, linguistic, and social backgrounds. The findings indicate that traditional interpretations of this verse are often patriarchally biased, positioning men as absolute leaders and women as subordinates. However, through a feminist tafsir approach, the verse can be read as an invitation to foster harmony and reciprocal responsibility in marital relationships, rather than as a legitimization of violence or dominance. This study asserts the critical need for a reformation of Islamic exegetical paradigms towards greater gender justice to support the formation of social systems free from violence and discrimination against women. Such reinterpretation also contributes to progressive Islamic legal discourse that protects women’s rights and encourages religious and educational institutions to adopt more critical and contextual approaches to religious texts.